Assessment of physical, chemical and energetic properties of sludge in industrial and municipal sewage treatment plant = Ocena właściwości fizycznych, chemicznych i energetycznych osadów pochodzących z oczyszczalni ścieków przemysłowych i komunalnych - Iżewska, Anna; Wołoszyk, Czesław; Sienkiewicz, Stanisław (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The work presents physical, chemical and energetic properties of sludge from industrial and municipal sewage treatment plant in West Pomeranian Voivodeship. Among many macronutrients, sludge contains much of the following: nitrogen, phosphorus, calcium and magnesium, but little potassium. Total content of heavy metals (Cd, Cr, Cu, Mn, Ni, Pb, Hg, Zn) was lower than norms admitting sludge for natural, including agricultural use, presented in the Order of Ministry of the Environment14.
Keywords: sewage sludge; properties of sludge; chemical composition of sludges; heat of combustion and calorific value of sludge; osady ściekowe; właściwości osadów; skład chemiczny osadów; ciepło spalania i wartość opałowa osadów